Frequency and characterization of RHD variant alleles in a population of blood donors from southeastern Brazil: Comparison with other populations. (August 2021) - Rodrigues, Evandra Strazza; Romagnoli, Aline Cristina; Santos, Flávia Leite Souza; Cutter, Talitha Baldin; Catelli, Lucas Ferioli; Cédric, Vrignaud; Peyrard, Thierry; Covas, Dimas Tadeu; de Castilho, Lilian Maria; Kashima, Simone
Abstract: Background: The correct determination of D antigen could help to avoid alloimmunization in pregnant women and patients receiving blood transfusions. However, there are limitations in the identification of D variants as the partial and weak D phenotypes make the determination of D antigen a great challenge in the transfusion routine.' Study design and methods: The molecular characterization of D variants was performed on blood donors from southeastern Brazil with atypical D typing. Furthermore, the serological profile of all RHD variant alleles identified was analyzed using different Anti-D clones. The prevalence of RHD alleles and genotypes found was compared with those described in other countries and in other regions from Brazil. Results: Atypical serologic D typing occurred in 0.79 % of blood donors. The majority of RHD variant alleles (88 %) were first characterized by multiplex PCR and PCR-SSP as RHD*weak partial 4 (47 %), followed by RHD*weak D type 3 (29.9 %), RHD*weak D type 2 (3.9 %) and RHD*weak D type 1 (3.1 %). Genomic DNA sequencing characterized the RHD*weak partial 4 variants found in RHD*DAR1.2 (weak 4.2.2) (22 %), RHD*DAR3 (weak 4.0.1) (2.4 %), RHD*DAR3.1 (weak 4.0) (22 %) and RHD*DAR4 (weak 4.1) (0.8 %). RHD variant alleles associated with partial D, such as, RHD*DAU-4 (1.6 %), RHD*DAU -5 (2.4 %), RHD*DAU-6 (1.6 %), RHD* DIII type 8 (1.6 %), RHD*DVII (3.9 %) and RHD* DMH (0.8 %) were also observed. Conclusion: The prevalence of RHD variant alleles observed in this cohort differ from those found in other populations, including Brazilians from other regions. RHD allele distribution in specific regions should be considered for implementation of algorithms and genotyping strategies aiming at a more effective and safe transfusion.